Dampak Literasi Keuangan Terhadap Perilaku Keuangan Mahasiswa: Studi Kasus di Universitas HKBP Nommensen Pematang Siantar - Gultom, Binsar Tison; HS, Sahat Renol; Siagian, Lasma (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the description of financial literacy and financial management behavior, as well as the influence of financial literacy on financial management behavior of students at HKBP Nommensen Pematangsiantar University, especially Economic Education Study Program. The population in this study were all students majoring in economics education, totaling 300 students, which was then determined as a sample of 75 students using random sampling technique. The data collection methods used in this research are as follows: 1) Questionnaire, 2) Observation, 3) Documentation Study. The prerequisite test in this study is the normality test of the data using the Kolmogrov-Smirnov Test. The data analysis technique used is descriptive analysis and simple linear regression. The result of this study is that financial literacy has a positive and significant influence on the financial behavior of students at the HKBP Nommensen University Pematang Siantar, especially the Economics Education Study Program. Furthermore, financial literacy contributes 41.4% to the financial behavior of students while another 58.6% is explained by other variables outside of this study